The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-46702002000200012
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento voltamétrico da redução de 2-furfuraldeído em etanol utilizando eletrodo de carbono vítreo

Abstract: Este estudo descreve o comportamento voltamétrico da redução de 2-furfuraldeído em etanol utilizando-se eletrodo de carbono vítreo, visando estabelecer condições experimentais adequadas para a determinação de 2-furfuraldeído em álcool combustível. Os voltamogramas obtidos para o 2-furfuraldeído em uma velocidade de varredura (v) de 100mV.s-1 apresentaram uma corrente de pico catódica (i pc) definida em um potencial de -1,45V (vs. ECS) para o meio aquoso e -1,71V (vs. ECS) para o meio alcoólico, não sendo obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…No backward anodic peak has been observed in this range of scan rates. The linear decreasing of the ip,c/√(logVscan) ratio as a function of the cathodic shift of the Ep,c peak suggests a kinetic control on the overall electrochemical process [35]. The replacement of water with methanol as solvent did not cause meaningful changes in the morphology of the main cathodic peak previously observed.…”
Section: Electrochemical Behavior Of Hmfmentioning
confidence: 61%
See 1 more Smart Citation
“…No backward anodic peak has been observed in this range of scan rates. The linear decreasing of the ip,c/√(logVscan) ratio as a function of the cathodic shift of the Ep,c peak suggests a kinetic control on the overall electrochemical process [35]. The replacement of water with methanol as solvent did not cause meaningful changes in the morphology of the main cathodic peak previously observed.…”
Section: Electrochemical Behavior Of Hmfmentioning
confidence: 61%
“…No backward anodic peak has been observed in this range of scan rates. The linear decreasing of the i p,c / √ (logV scan ) ratio as a function of the cathodic shift of the E p,c peak suggests a kinetic control on the overall electrochemical process [35].…”
Section: Electrochemical Behavior Of Hmfmentioning
confidence: 93%
“…Voltammetric based analytical methods are used mainly for determination of organic compounds while stripping voltammetric-based methods are used mainly for quantification of transition metal ions. Working electrodes used in voltammetric methods are mainly based on carbon materials, such as glassy carbon [118,119,121,124], screenprinted carbon electrode [120] and carbon paste electrode [126]. In stripping voltammetric-based methods there is a prevalence of chemically modified carbon paste electrodes which are characterized by a superior ability to preconcentrate the analyte at electrode surface.…”
Section: Alternative Electroanalytical-based Methodsmentioning
confidence: 99%
“…All these voltammetric methods allow the quantification of acetaldehyde in a very sensitive way with low detection limits. The only working proposing a direct voltammetric method for quantification of an aldehyde without chemical derivatisation was presented by Saczk et al [124]. These authors have studied the voltammetric reduction of furfuraldehyde in ethanol media using a glassy carbon electrode.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…This has allowed the development of a HPLC method with amperometric detection able to quantify these aldehydes and ketones simultaneously in fuel ethanol 8. 2‐furfuraldehyde is the only aldehyde whose direct electrochemical reduction onto glassy carbon in ethanol media is described 9. It was observed that the electrochemical reduction of 2‐furfuraldehyde produces a voltammetric peak at −1.71 V vs. SCE in ethanol containing LiCl or LiOH as supporting electrolyte.…”
Section: Liquid Biofuelsmentioning
confidence: 99%